Formal [3 + 2] cycloaddition of α-unsubstituted isocyanoacetates and methyleneindolinones: enantioselective synthesis of spirooxindoles. Issue 1 (27th October 2016) - Peng, Xiao-Jiao; Ho, Yee Ann; Wang, Zhi-Peng; Shao, Pan-Lin; Zhao, Yu; He, Yun
Abstract : The first formal [3 + 2] cycloaddition of α-unsubstituted isocyanoacetates with methyleneindolinones was developed. A variety of optically enriched 3, 3′-pyrrolidinyl spirooxindoles were obtained. Abstract : The first enantioselective formal [3 + 2] cycloaddition of α-unsubstituted isocyanoacetates with protecting-group-free methyleneindolinones was developed. A variety of optically enriched 3, 3′-pyrrolidinyl spirooxindoles were obtained in excellent yields, and diastereo- and enantioselectivities (up to 99% yield, >20 : 1 dr, 99% ee) with low catalyst loading under mild reaction conditions.